ANALYSIS OF OPTIMIZATION STRATEGIES FOR HUMAN RESOURCES IN CHINESE UNIVERSITIES - Hongrui, Wen; Wangthanomsak, Mattana; Somsuptrakul, Sukanya (วารสารนิสิตวัง, 2025)
As a key base for talent cultivation, universities must fully recognize human resource management’s importance. Scientific and reasonable management strategies can significantly improve the overall efficiency of human resource allocation, laying a solid foundation for university teaching work. This article is based on the current situation of human resource management in universities, and explains the "Pareto optimality" state of human resources in management theory. It delves into the prevalent issues within university human resource management and suggests that universities strategically bolster the integration of information technology and meticulous talent management, emphasizing talent cultivation and development to provide valuable reference ideas and useful insights for the reform and innovation of human resource management in universities.